The Business Development Strategy of Jamu at PT. Firdaus Kurnia Indah (FKI) in Bangkalan Regency - Pratiwi, Yunita Eka Dyah; Setiani, Setiani; Kurniyanto, Ifan Rizky (Tropical Biopharmaca Research Center, IPB University, 2024)
Jamu is a traditional medicine that Indonesians have consumed for generations. Several herbal medicine industries in the Bangkalan district have difficulty surviving and developing their businesses. This study aims to determine the strategy for developing the herbal medicine business at PT. FKI, Bangkalan. This research is part of the MBKM-KWU UTM Agricultural Agribusiness Study Program in 2022, which is carried out in the form of a one-month internship as preliminary research. Data was collected from March to June 2023 using questionnaires and deep interviews with respondents. The 4C diamond, SWOT, and QSPM analysis are used to determine strategies that can be implemented for PT. FKI. Internally, the main strength is using natural ingredients, and a shortage of product stock is the main weakness. Assessment of external factors reveals that technological progress, especially social media, is the main opportunity, while the main threat faced is the existence of similar competitors. PT. FKI is in an aggressive strategic position to increase competitiveness by exploiting the company's opportunities and strengths.